Integrasi Nilai Moderasi Beragama di Tengah Masyarakat Multikultural dalam Tradisi Santunan Anak Yatim: Studi Sosial Keagamaan di Era Kontemporer - Rojiid Arbi Muhyardho; Zahda Hermalia Hasanah; Ahmad Raihan Bahrul Ilmi; Nasik Fikri Haidary; Nur Hidayatus Sholihah; Ayu Dwi Puspita Rani; Devina Mita SasQia; Cahya Fadilla Fajrianti; Anisa Putri Maulidya; Amal Agus Mahardika (Lembaga Pengembangan Kinerja Dosen, 2025)
This article explores the integration of religious moderation values within the tradition of orphan charity (santunan anak yatim) in a multicultural community. Conducted as part of a community service program (Kuliah Kerja Mahasiswa) by ten students from Universitas Islam Negeri Maulana Malik Ibrahim Malang, this study took place in Sumberkradenan Village, Pakis Subdistrict, Malang Regency, East Java. Using a qualitative descriptive approach through interviews, observation, and documentation, the research uncovers how a routine act of religious compassion becomes a powerful medium for fostering social harmony, tolerance, and interfaith cooperation. The findings reveal that orphan charity is not merely a religious obligation but also a social practice that embodies the spirit of inclusiveness, solidarity, and mutual respect across diverse religious and cultural groups. This study highlights the potential of local religious traditions as grassroots models for promoting religious moderation in contemporary society.